2018
DOI: 10.1039/c8fd00002f
|View full text |Cite
|
Sign up to set email alerts
|

The electronic properties of Au clusters on CeO2 (110) surface with and without O-defects

Abstract: We use density functional theory with Hubbard corrections (DFT+U) to understand the local electronic properties of Au adatom and Au 2 dimer adsorption on the CeO 2 (110) surface. We show that, based on the initial geometries, we can observe Au species in . We present a detailed discussion using Bader charge analysis and partial density of states to support our observations. We also discuss the influence of solvent on the adsorption of Au adatoms adsorbed on top of an O-vacancy, which shows interesting geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…Therefore, in this study we have only investigated the configurations which have the most negative Cu adsorption energies based on the DFT+U calculations, as listed in ESI Table 3, and compared the structures and energetics without (DFT+U) and with the van der Waals dispersion term (DFT+U+D3). We find that for each of the nine configurations investigated, the inclusion of the D3 term only makes the adsorption energies slightly more negative (maximum difference less than 0.23 eV) which agrees with the previous work 47,49,50 .…”
Section: Dispersion Correctionssupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, in this study we have only investigated the configurations which have the most negative Cu adsorption energies based on the DFT+U calculations, as listed in ESI Table 3, and compared the structures and energetics without (DFT+U) and with the van der Waals dispersion term (DFT+U+D3). We find that for each of the nine configurations investigated, the inclusion of the D3 term only makes the adsorption energies slightly more negative (maximum difference less than 0.23 eV) which agrees with the previous work 47,49,50 .…”
Section: Dispersion Correctionssupporting
confidence: 91%
“…In Case3, one Ce 3+ is a surface NN, while the other one is a surface NNN. Calculated oxygen vacancy formation energies are in the range of 0.98-1.43 eV, as reported in Table 4, which are slightly lower than those from previous work (1.54-2.69 eV) 2, 24, 44-46 , because of a more negative O 2 binding energy of -9.863 eV (bond length 1.233 Å) used in our work24,47 (ESI Section 1.5). The well-known error of overbinding O 2 using GGA/LDA DFT and PAW potentials24,46 , as well as different computational parameters used (e.g.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…Because ceria directly participates in the catalytic reaction, it is of great interest to further explore the influence of the support on the mode of operation. In addition to above-mentioned facet-dependent differences in the ease with which oxygen vacancies can be created, the exposed facet may affect the interactions between ceria and the supported gold ,, as well as between gas-phase molecules (CO, H 2 O) and the catalyst surface. ,,, Recently, we have examined structure–activity relations for CO oxidation over Au/rods (CeO 2 (110), CeO 2 (100)) and Au/cubes (CeO 2 (100)) using combined operando Raman/UV–vis spectra and DFT calculations, with the former showing higher low-temperature CO oxidation activity. In the following text, we will first illustrate important aspects of the facet-dependent behavior and then include our previous work on polycrystalline ceria supported gold in the discussion. ,, …”
Section: Au/ceria Catalysts: Support Participation and Structural Dyn...mentioning
confidence: 99%
“…13 The Aun/CeO2-X system has been the subject of several computational studies although most of them focussed on very small clusters. [14][15][16][17][18] Chutia et al 27 studied single gold atoms and demonstrated that electron transfer to the gold occurred over vacancies. Zhang et al investigated the structures and properties of Au clusters with up to 11 atoms, but all their structures were built under the precondition that one of the Au atoms is located at a vacancy site.…”
Section: Introductionmentioning
confidence: 99%